The Legal Framework for Unfair Competition in Mauritanian and Comparative Legislation (The International Journal for Scientific Research, 2026)
This research addresses the topic of "The Legal Framework for Unfair Competition in Mauritanian and Comparative Legislation," by studying its concept and distinguishing it from other similar systems and its legal framework. It highlights that unfair competition is represented by any commercial conduct that violates the law or professional norms and aims to harm competitors or mislead consumers. The research also presents its most important forms, such as creating confusion, misleading, undermining trust, and disclosing trade secrets. It shows that its legal basis is often based on the rules of tort liability based on fault, harm, and causation. It also clarifies the role of the judiciary in determining its scope due to its flexibility and development, and concludes with the need to strengthen the legal and regulatory framework to ensure the protection of fair competition and achieve balance within the market.
Keywords: Legal Framework; Competition; Consumer; Market; Trade